Spontaneous Rupture of Uterine Veins In Pregnancy (Bangladesh Journal of Obstetrics & Gynaecology, 2013)
Spontaneous rupture of uterine vessels during pregnancy is a rare cause of shock that has a  high rate of maternal and foetal loss. Though the usual presentation is of maternal shock, it  is necessary to have in mind that possibility of blood vessels rupture may be in cases of  abdominal pain & hypotension of unknown origin during pregnancy. In such an event an exploratory laparatomy followed by caesarean with ligation of the uterine  vessel or its branch can help in preventing a maternal mortality. The advent of modern  resuscitative facilities, anaesthesia techniques have lowered mortality associated with this condition from 49% to 3.6%. DOI: http://dx.doi.org/10.3329/bjog.v25i2.13745 Bangladesh J Obstet Gynaecol, 2010; Vol. 25(2) : 85-86